2020
DOI: 10.3389/fphar.2020.01220
|View full text |Cite
|
Sign up to set email alerts
|

A Potent Antioxidant Endogenous Neurohormone Melatonin, Rescued MCAO by Attenuating Oxidative Stress-Associated Neuroinflammation

Abstract: Ischemic stroke is an acute neurological syndrome either due to permanent or temporary obstruction of blood. Such obstruction immediately triggers abrupt pathological cascading processes, which collectively lead to neuronal cell death. Oxidative stress and neuroinflammation in ischemic stroke are critical regulating events that ultimately lead to neuronal death. Complicated interplay exists between the two processes which occur through several stages. Most often, oxidative stress precedes the inflammatory mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 66 publications
(80 reference statements)
0
16
0
Order By: Relevance
“…β-actin was used as a loading control. 45,46 The following day, membranes were incubated with secondary antibodies, and western bands were visualized on x-ray film using ECL detection reagent following the instructions of the manufacturer (Amersham Pharmacia Biotech, Piscataway, NJ, United States).…”
Section: Western Blotmentioning
confidence: 99%
“…β-actin was used as a loading control. 45,46 The following day, membranes were incubated with secondary antibodies, and western bands were visualized on x-ray film using ECL detection reagent following the instructions of the manufacturer (Amersham Pharmacia Biotech, Piscataway, NJ, United States).…”
Section: Western Blotmentioning
confidence: 99%
“…Moreover, the low energy values and relatively higher hydrogen bond formation further enhanced complex stability, as revealed through the molecular docking analysis. Additionally, previous studies have reported that targeting inflammation and oxidative stress-coupled targets could provide better therapeutic outcomes ( Ali T et al, 2020 ; Ling et al, 2020 ), which opens several avenues for the use of natural drug substances.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, role of the JNK pathway in inflammatory cascades and cellular death has been strongly established ( Ali A et al, 2020 ), and ROS and inflammatory cytokines can trigger JNK activation ( Ali A et al, 2020 ; Ali T et al, 2020 ; Ling et al, 2020 ). Furthermore, the p-JNK pathway has been implicated in various animal models and human diseases ( Shah et al, 2018 ; Li and Liu, 2019 ; Ali A et al, 2020 ; Ling et al, 2020 ; Malik et al, 2020 ), and the downregulation or inhibition of this pathway has been found to contribute to the protective strategy ( Shah et al, 2019 ). We observed similar activities in the APAP-intoxicated group, and carveol significantly reduced p-JNK expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin was reported to play important roles in the pathophysiological components of cellular injury after ischemic stroke via modulating oxidative stress, mitochondria, apoptosis, inflammatory response, melatonin receptors 1/2, circular RNA in ischemic injury (Kilic et al, 2020). For example, in a focal cerebral ischemic injury rat model, melatonin reduced brain infarction associated with sequentially rescued neuronal apoptosis and attenuated neuroinflammatory response by modulating oxidative stress signaling (NF-jB/COX2/iNOS) and enhancing anti-oxidative systems such as Nrf2/HO-1/Trx (Ling et al, 2020). But, the cellular mechanisms whereby melatonin protects against stroke-induced neuronal damage are not yet fully clear.…”
Section: Discussionmentioning
confidence: 99%